2019
DOI: 10.1186/s13765-019-0419-3
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of antioxidant and antimicrobial activity of phenolic lipids produced by the transesterification of 4-hydroxyphenylacetic acid and triglycerides

Abstract: Several phenolic compounds derived from plant biomass are attracting attention because they display high antioxidant activity. In this study, antioxidant activity was confirmed in 4-hydroxyphenylacetic acid (HPA), and transesterification reaction using Candida antarctica lipase B was performed to enhance the solubility of HPA. The HPA-diolein (HPA-DON) was synthesized from HPA and triolein, while the HPA-fish oil diglyceride (HPA-dFO) was synthesized from HPA and Menhaden fish oil. To increase the conversion y… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
8
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 15 publications
(9 citation statements)
references
References 28 publications
0
8
0
1
Order By: Relevance
“…Jang et al [57] also reported nonanoic acid's antifungal potential. Sari et al [58] showed that 4-hydroxyphenylacetic acid has antioxidant potential, whereas resorcinol and its derivatives were demonstrated to have antifungal activities by Karunanayake et al [59]. Antifungal resorcinols have been implicated in the quiescence of C. gloesoporioides and A. alternata on mango [60].…”
Section: Discussionmentioning
confidence: 99%
“…Jang et al [57] also reported nonanoic acid's antifungal potential. Sari et al [58] showed that 4-hydroxyphenylacetic acid has antioxidant potential, whereas resorcinol and its derivatives were demonstrated to have antifungal activities by Karunanayake et al [59]. Antifungal resorcinols have been implicated in the quiescence of C. gloesoporioides and A. alternata on mango [60].…”
Section: Discussionmentioning
confidence: 99%
“…2,2 -Azino-bis(3-ethylbenzothiazoline-6-sulphonic acid) (ABTS) radical scavenging activity was evaluated as described previously [19]. Briefly, ABTS dissolved in phosphate buffer was added to potassium persulfate solution.…”
Section: Antioxidant Activitiesmentioning
confidence: 99%
“…An ABTS assay was conducted as described previously, with some modifications [ 30 ]. ABTS radical cation (ABTS •+ ) solution was produced by reacting a 7 mM ABTS stock solution with 2.45 mM potassium persulfate (1:1, v / v ) for 16 h before use, and the solution was diluted with methanol to obtain a starting absorbance of 0.77 at 734 nm.…”
Section: Methodsmentioning
confidence: 99%